Gene variability in matrix metalloproteinases in patients with recurrent aphthous stomatitis - Slezakova, Simona; Borilova Linhartova, Petra; Bartova, Jirina; Petanova, Jitka; Kuklinek, Pavel; Fassmann, Antonin; Dusek, Ladislav; Izakovicova Holla, Lydie (Journal of oral pathology & medicine, 2020)
Background The development of recurrent aphthous stomatitis (RAS), inflammatory disease of oral mucosa, is influenced by both environmental and genetic factors. The aim of this study was to investigate polymorphisms located in seven genes coding different types of matrix metalloproteinases (MMPs)—collagenases (MMP1, MMP8, and MMP13), gelatinases (MMP2 and MMP9), stromelysin (MMP3), and membrane‐type metalloproteinase (MMP16) in patients with RAS and healthy controls. Methods Totally, 223 subjects were included in this case‐control study and their detailed anamnestic, clinical, and laboratory parameters were recorded. Seventy‐seven patients with RAS and 146 controls were genotyped for seventeen polymorphisms in the MMPs genes using the real‐time polymerase chain reaction (PCR) or PCR with restriction analysis. Results Allele, genotype, and haplotype frequencies of the studied polymorphisms between RAS patients and controls were similar, except for allele distributions of MMP1 rs1144393, MMP9 rs3918242, and MMP16 rs10429371, which were different between patients with RAS and healthy controls (P = .023, P = .049 and P = .025, all Pcorr > 0.05, respectively). Moreover, the comparison of genotype frequencies (TT vs CC + CT) of the MMP16 rs10429371 variant showed a marginally significant difference between RAS patients and controls (P = .05, Pcorr > 0.05, OR = 1.68, 95% CI = 0.95‐2.98). Conclusions No significant relationship between investigated polymorphisms in seven MMPs genes and RAS development in the Czech population was observed in this study.